Deficiencies in the System of the European Union Agency for Fundamental Rights - (:unkn) unknown (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2018)
The European Union Agency for Fundamental Rights (FRA), which was established 10 years ago, is the only body of the European Union, which is concerned specifically with fundamental rights issue. The Agency provides to the EU institutions, bodies, offices and agencies and its Member States, when implementing EU law, assistance and expertise relating to fundamental rights issues in order to support them when they take measures or formulate courses of action within their respective spheres of competences in order to fully respect fundamental rights. Since its inception in 2007, the Agency, which deals with fundamental rights across the EU through its opinions, reports, handbooks, surveys and similar works, has confronted many critics. Some of them have survived until now. The focus of the manuscript, within the context of such critics, is to identify deficiencies in the system of the Agency.
Keywords: European Union Agency for Fundamental Rights; Fundamental Rights; Deficiencies in the System of the European Union Agency for Fundamental Rights; EU